Citral: antifungal activity and mode of action, against Cladosporium oxysporum - Menezes, Camilla Pinheiro de; Medeiros, Cássio Ilan Soares; Lima Perez, Ana Luíza Alves de; Sousa, Janiére Pereira de; Pinheiro, Lilian Sousa; Oliveira Filho, Abrahão Alves de; Lima, Edeltrudes de Oliveira (Ciência e Natura, 2020)
Dematiaceous fungi are a group of fungi with dark colonies and pigmented fungal elements. The spectrum of diseases associated with fungi ranges from superficial skin and soft tissue infections to disseminated sepsis with high mortality. Therefore, it is necessary to study molecules with an antifungal action against these fungis. Attention has been drawn to the antimicrobial activity of aromatic compounds because of their promising biological properties. Citral is a monoterpene with known pharmacological properties, including antimicrobial action. Therefore, we investigated the antifungal activity of citral against strains of C. oxysporum, which involved determining its minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC) and effects on mycelial growth and conidial germination. The effects of citral on the cell wall (sorbitol protect effect) and the cell membrane (citral to ergosterol binding) were investigated. Citral inhibited the growth of 50% of C. oxysporum strains employed in this study at an MIC 128μg/mL, as well as mycelial growth and conidia germination.